Utilization of 4-Chloro-7-Nittobenzo-2-Oxa-1, 3-Diazol (NBD-CL) as Chromogenic Reagent for Determination of Metformin hydrochloride (MET) in Pharmaceutical Formulation - Elbashir, Abdalla Ahmed; Abdallah alfaki, Omnia mohamed (Asian Journal of Pharmaceutical Research and Development, 2019)
A new, simple, selective, precise and accurate spectrophotometric method for the determination of metformin in pharmaceutical formulation was developed and validated. The method was based on the reaction between metformin and 4-chloro-7-nitrobenzo-2-oxa-1,3-diazole (NBD-Cl) at alkaline medium (pH 12.0) to form brown adduct. Beer’s law was obeyed in the concentration range of 20-100 μg mL-1 of metformin at maximum wave length 465 nm . Under the optimized reaction conditions, the linear regression equation of the calibration curve was found to be y=0.003x +0.156 with a linear correlation coefficient (r=0.999). The limit of detection (LOD) and limit of quantification (LOQ) were found to be 5.8, 17.5 μg mL-1 respectively. The method is useful for routine analysis of metformin in quality control laboratories.